KEBERADAAN HAK ADAT DALAM PEMANFAATAN SARANG BURUNG WALET DI HABITAT ALAMI: ANTARA HARAPAN DAN KENYATAAN - Wahyono, Ary (Jurnal Masyarakat dan Budaya, 2005)
Existency of adat community in reources use found in state constitution. On the contrary, regulation of nest Swiflets of Collacia not including in support of communal property rights. In one hand, privatization of nest swiflets of Collacia pay attention to solution for depletion of these genus. But in other hand, privatization had ignored communal property rights. Adat community should be substute the state for control of nest swiflets of Collacia used in natural environment